Meningkatkan Budaya Membaca Melalui Literacy Cloud - Afip Miftahul Basar (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The current era of globalization affects various sectors of life which are massively marked by the use of technology. As a result of globalization, many individuals who are capable of knowledge and insight are born, and produce individuals with the term digital native, namely where the internet is an integral part of the lives of generations living in the digital era. Within the setting of instruction, the advancement of innovation and the web ought to have had a positive affect on the learning handle as well as from the viewpoint of educator proficient development. Conditions at SDN 1 Karawang Wetan, SDN 1 Palubonsari, and SDIT MTA Karawang, where the culture of reading or digital-based literacy needs to be improved. The solution to overcome these problems is the reading movement program through the Literate School Ecosystem program, which is defined as a movement to motivate, mobilize, and cultivate reading digitally, which is carried out with a participatory persuasive approach. The method used is descriptive qualitative with data sources in the form of interviews, literature review, field notes and observations. This activity consists of three treatments in the form of training, assistance with digital information retrieval strategies, and application of fun reading to children. This activity program has succeeded in increasing digital literacy, where the evaluation results show teachers are able to search for digital information, and apply fun reading to students.